Indigeneity and the Indo-Caribbean in Cyril Dabydeen’s Dark Swirl - Khan, Aliyah (Studies in Canadian Literature, 2015)
Indo-Guyanese Canadian writer and poet Cyril Dabydeen’s novel Dark Swirl (1988) imagines the settler-colonial cultural and environmental encounter among a rural Indo-Guyanese family, the indigenous reptilian water spirit the massacouraman, and a white British naturalist, illustrating that the Indo-Caribbean story of migration, indenture, and postcolonial citizenship includes negotiation not only with the Afro-Caribbean, but with the marginalized Indigenous presence in the Caribbean. This essay considers, among other aspects of Dabydeen’s novel, the metaphor of water and the bridging of the relational gap between Indigenous myth and Indo-Guyanese Hinduism through similar stories of reptilian spirits to argue that, like Afro-Guyanese, Indo-Guyanese are interpellated into the nation and accorded postcolonial sovereignty through the appropriation of Indigenous myth and the syncretism of religious and folkloric belief. Following the Guyanese writer of magical realism Wilson Harris, Dabydeen’s unusual literary attention to the relationship between the Indigenous Caribbean and creolized diasporic communities illustrates that postcolonial rulers invoke continuity with an effaced Indigenous presence to establish legitimacy while simultaneously denying living Indigenous inhabitants their land rights and identities.